The Impact of the Construction Industry on the Social and Economic Development of Territories - SEROGINA, D.; PUSHKAR, T.; ZHOVTIAK, H. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2022)
The article’s objective is to show the results of an analysis of the relationship between the construction industry and social and economic development of territories. Construction projects have great potential to promote social and economic development as drivers of growth. The construction industry is a basic and diversified sector of the economy, which involves a wide range of stakeholders and has developed links with other areas of activity. The industry creates investment opportunities in related sectors and is vital to achieving national social and economic goals. This research is devoted to the study of the state of the construction industry as a key indicator of the level of development and efficiency of modernization processes in the economy of the regions. The article formulates conclusions and offers guidelines for the development of the construction industry as a factor in economic growth. It is concluded that the current state of the construction industry is of paramount importance, which indicates the well-being, health and quality of life of citizens, is the basis of economic growth of any country, and therefore affects the role of each sector at all levels of the economy. The construction sector has a direct impact on the social and economic development of money circulation, so the lack of proper construction infrastructure leads to an underdeveloped economy, low living standards and unbalanced income distribution, which are factors contributing to the country’s economic decline. Effective management of the construction sector leads to improved quality of life, including the promotion of tourism, a sustainable environment, money circulation and job creation across the country.